A Review of AI and ML Adoption in Businesses Worldwide - Nithyananda B Devadiga, (International Journal of Scientific Research in Science and Technology, 2024)
Artificial Intelligence (AI) and Machine Learning (ML) are the two emerging technologies adopted by most of the business companies worldwide. The use of advanced technologies is highly effective on businesses and capable of improving overall performance of companies. Examining the potential effects, opportunities, challenges and scopes of adopting AI and ML in businesses worldwide is the main purpose of this study. In regard to this, secondary qualitative methods have been used for gathering authentic and reliable data from several scholarly articles and peer-reviewed journals. All the findings are discussed briefly and it has been identified that AI and ML have great influence towards workplace efficiency, productivity and profitability of business companies. It also helps to boost customer satisfaction and gain competitiveness in the global market.
Keywords: AI; Business Development; ML; Emerging Technology; Digitalisation; Sustainable Development